Pengaruh Ukuran Biji Kopi Robusta pada Kualitas Citarasa Kopi - Widyasari, Ayu; Warkoyo, Warkoyo; Mujianto, Mujianto (Jurnal Agro Industri Perkebunan, 2023)
Robusta coffee is known for its bitter taste and stronger aroma compared to arabica coffee. Additionally, robusta coffee has a higher caffeine content. Coffee quality is evaluated based on the quality of green coffee beans and the taste of the brewed coffee. A good and delicious coffee taste can be achieved by roasting the coffee beans correctly and using high-quality green coffee beans. This study was conducted to evaluate the taste of quality 1 robusta coffee beans with different sizes - L (7.5 mm in diameter), M (6.5 mm in diameter), and S (5.5 mm in diameter). The experiment was carried out using a simple randomized block design and analyzed using analysis of variance, followed by the LSD test with a 5% significance level. The research was conducted at a coffee processing factory in Satak village, Kediri, East Java in March 2022. The taste testing of the robusta coffee was done using the cupping test method according to the Specialty Coffee Association of America (SCAA) standards. The results of the analysis indicate that the taste of quality 1 robusta coffee beans is significantly affected by the size of the beans in terms of fragrance, flavor, balance, sweetness, and overall taste. Based on the cupping coffee quality classification scores, robusta coffee beans 1S, 1M, and 1L scored <75, which means they are of low quality and considered off-grade.